Reinforcement of Quaternary Ammonium Modified Silica (QAMS) with Magnetite and its Application by Solid Phase Adsorption (SPA) to Adsorb Chromate Ions - Ngatijo Ngatijo; Restina Bemis; Abdul Aziz; Rahmat Basuki (Jurnal Kimia Sains dan Aplikasi, 2020)
Chromium (VI) in the form of chromate anions that have toxic properties needs to be overcome. This study aims to reinforce cationic sorbent quaternary amine-modified silica with magnetite (QAMS-Fe3O4) to adsorb chromate ions. QAMS prepared by reflux methylation ammine modified silica (AMS) obtained from destruction silicate from rice husk ash followed by the addition of 3-APTMS. Characterization QAMS-Fe3O4 by FT-IR showed successfully of methylation process indicated by disappearing absorbance at 1388 cm-1, and emerging absorbance at 2939 cm-1 in QAMS and QAMS-Fe3O4 indicated a transformation of N-H from -NH2 group to [-N+(CH3)3]. XRD analysis denotes 2θ = 30.15°, 35.53°, 43.12°, 57.22°, and 62.90° (JCPDS No. 00-033-0664) fathomed as a characteristic peak of magnetite. SEM-EDX reveals the homogenous topological spherical form with an average particle size 0.006 µm that is dominated by Si element (52.81%) with magnetic moment value = 34.1 emu/g. The stability test shows that this material stable in an acid condition. The adsorption of chromate ions was conducted by the SPA method. Optimal pH obtained by pH range 4-7 with more than 90% adsorbed chromate ions. Variation of increasing series flow rate from 0.05 to 1.5 mL min-1 resulted in decreased adsorbed chromate ions. The use of SPA methods offered simpler and easier handling than the batch method without overriding the adsorption process effectiveness.